Xu, Bin. The politics of compassion: the Sichuan earthquake and civic engagement in China. xiv, 237 pp., map, illus., bibliogr. Stanford: Univ. Press, 2017. £20.99 (paper) - Paltemaa Lauri (Wiley-Blackwell Publishing Ltd., 2022)
A book review of Xu Bin's The politics of compassion: the Sichuan earthquake and civic engagement in China (2017).